2021
DOI: 10.1088/1361-6528/ac0ead
|View full text |Cite
|
Sign up to set email alerts
|

Design of an electric-driven nonvolatile low-energy-consumption phase change optical switch

Abstract: Traditional optical switches relying on the weak, volatile thermo-optic or electro-optic effects of Si or SiN waveguides show a high consumption and large footprint. In this paper, we reported an electric-driven phase change optical switch consisting of a Si waveguide, Ge 2 Sb 2 Te 5 (GST) thin film and graphene heater suitable for large-scale integration and high-speed switching. The reversible transition between the amorphous and crystalline states was achieved by applying two different voltage pulses of 1.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…[102] While more detailed studies are required to develop and demonstrate a fully functional silicon-integrated device, the non-volatile property of VO 2 at room temperature using the first major transition between insulator state and oscillating state reported for the first time paves the foundation to unleash the latching property of VO 2 -based integrated optical switches. [102] An electrical-driven phase change optical switch consisting of a Si waveguide and GST film with ITO or graphene heaters was reported by Li et al [97] in 2021. Different from the previous works, [92,93,100] which use VO 2 as the PCM and use Ti heater or square optical pump pulse to trigger the phase transition, this optical switch uses GST as PCM and uses ITO or graphene heaters to trigger the phase transition.…”
Section: Silicon Integrated Optical Switches With Pcm Based On the Wa...mentioning
confidence: 99%
See 2 more Smart Citations
“…[102] While more detailed studies are required to develop and demonstrate a fully functional silicon-integrated device, the non-volatile property of VO 2 at room temperature using the first major transition between insulator state and oscillating state reported for the first time paves the foundation to unleash the latching property of VO 2 -based integrated optical switches. [102] An electrical-driven phase change optical switch consisting of a Si waveguide and GST film with ITO or graphene heaters was reported by Li et al [97] in 2021. Different from the previous works, [92,93,100] which use VO 2 as the PCM and use Ti heater or square optical pump pulse to trigger the phase transition, this optical switch uses GST as PCM and uses ITO or graphene heaters to trigger the phase transition.…”
Section: Silicon Integrated Optical Switches With Pcm Based On the Wa...mentioning
confidence: 99%
“…On top of the corrugated waveguide, GST nano-strips is integrated. The straight silicon waveguide has a width (W 1 ) of 370 nm, and the grating-assisted waveguide (loaded with GST) has a basic width [97] Copyright 2022, IOP Publishing Ltd.…”
Section: Silicon Integrated Optical Switches With Pcm Based On the Wa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Such appealing properties have led to developing high-performance and new kinds of waveguide-based photonic integrated devices such as modulators 26 – 30 , pass polarizers 31 , photonic memories 32 37 , reconfigurable devices 38 40 , switches 41 47 , or synapses 48 . Thereby, enabling new applications based on non-von Neumann architectures such as arithmetic 49 and logic 50 operations, in-memory computing 51 , neuromorphic computing 52 , 53 , or photonic tensor cores 54 .…”
Section: Introductionmentioning
confidence: 99%
“…With further research, more and more new materials and structures have been discovered, such as inorganic perovskite [ 14 ], black phosphorus [ 15 ] and phase-change materials [ 16 ], etc. Among them, phase-change materials (PCMs) are one of the ideal candidates in the field of integrated photonics and have become a hot topic in the research of optical switches [ 17 ], optical modulators [ 18 ], optical computing [ 19 , 20 ] and optical neural networks [ 21 ]. Cheng et al [ 22 ] demonstrated a photonic synapse based on an integrated PCMs-Si waveguide in 2017, where the weight of the synapse can be set by the light pulse.…”
Section: Introductionmentioning
confidence: 99%